Plateformes de billetterie : une nouvelle étape dans l’industrialisation de la musique vivante ? - Philippe Bouquillion; Olivier Thuillas; Louis Wiart (Communiquer)
Important industrial movements are at work within live music in France, and those are articulated around ticketing platforms. There is a process of industrializing the sector, which appeared quite clearly through the three industrializing trends of technologization, rationalization, and ideologization. In fact, the ticketing activity is at the heart of the strategies developed by large groups, which contributes inserting live music into financial and industrial dynamics, thus giving them a particularly significant market power. However, music professionals, and more specifically live music stages and operas, seek to reclaim ticketing services in order to maintain control over their data while keeping close ties with their audience.